IMF Quota and Governance Reform : Elements of an Agreement. (Policy Papers; Policy Paper ;, 2010)
This paper sets out, and seeks to make operational, a core package for the consideration of the Executive Board and, subsequently, the Board of Governors. The reforms would lead to a major overhaul of the Fund's quotas and governance, strengthening the Fund's legitimacy and effectiveness. The paper proposes completion of the 14th General Review of Quotas with a doubling of quotas and a major realignment of quota shares among members. It also covers proposals that would lead to a more representative, all-elected Executive Board.